Podcast Sebagai Media Dakwah Era Pandemi - Panji Putra Ariyanto (Academic Journal of Da'wa and Communication, 2021)
This research wants to know the potential use of podcasts as providers of da'wah content. Da'wah is one of the mandatory processes of humans in living their lives. Da'wah activities will experience changes and adjustments along with the development of human life. Da'wah is everything that can be done at any time, place and condition including in the Covid-19 pandemic. Podcasts become one of the alternative mediums of community or individual in spreading the treatises on Islamic values. This research used descriptive qualitative research method with literature study type. The conclusion of this research is that Podcasts are quite capable and suitable as a medium for disseminating da'wah with a note that they must develop relevant strategies that can improve their existences.